A nanocomposite photocatalytic material and preparation method thereof

By stacking the spherical titanium dioxide particles coated with graphene to form a block structure, the problems of limited specific surface area and low photocatalytic efficiency of existing photocatalytic materials are solved, and higher photocatalytic efficiency and air purification capabilities are achieved.

CN114618466BActive Publication Date: 2025-02-11XIFENG 2D FUJIAN MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011421769.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-08
Publication Date
2025-02-11
Estimated Expiration
2040-12-08

AI Technical Summary

Technical Problem

The existing graphene and titanium dioxide composite photocatalytic materials have limited specific surface area, insufficient photocatalytic efficiency, and limited loading in actual applications, which cannot meet the needs of air purification.

Method used

A nanocomposite photocatalytic material with a spherical titanium dioxide particles coated with graphene is stacked to form a block structure. The spherical titanium dioxide particles are bonded and stacked through hanging bonds on the surface of graphene to form a block with multiple internal and external hole structures connected to each other. structure, thereby increasing the specific surface area.

Benefits of technology

The specific surface area and photocatalytic efficiency of photocatalytic materials are improved, the load capacity and air purification capacity on the substrate are enhanced, and the bacteria and viruses in the air can be rapidly degraded, and the removal rate of the air purification system is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114618466B_ABST
    Figure CN114618466B_ABST
Patent Text Reader

Abstract

The invention discloses a nano-composite photocatalytic material, which is a block structure formed by stacking a plurality of spherical titanium dioxide particles with graphene coated on the surface; the block structure is a plurality of hole structures connected inside and outside formed by mutually stacking the spherical titanium dioxide particles with graphene coated on the surface; the spherical titanium dioxide particles with graphene coated on the surface comprise an inner spherical titanium dioxide layer and an outer graphene coating layer; the spherical titanium dioxide particles with graphene coated on the surface are bonded to each other through dangling bonds on the graphene surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocomposite materials and photocatalysis, and in particular to a nanocomposite photocatalytic material and a preparation method thereof. Background Art

[0002] Photocatalytic purification materials are materials that, under the action of a certain light source, electrons in the valence band (e - ) jumps to the conduction band, generating corresponding holes (h + ), which generates superoxide ion free radicals, hydroxyl free radicals and superoxide hydroxyl free radicals with extremely strong oxidizing effects, and can oxidize and decompose formaldehyde, benzene, toluene, xylene, ammonia, VOC and other toxic and harmful gas pollutants, odors, bacteria, etc. into harmless CO2 and H2O, and has high-efficiency and broad-spectrum disinfection performance, and has a good inhibitory and killing effect on various common pathogens.

[0003] But traditional photocatalytic materials only have high quantum conversion efficiency at the nanometer size, and the smaller the size of the nanomaterial, the higher its photocatalytic efficiency. For example, the degradation efficiency of P5 (the average particle size of the particles is about 5nm) particles in solution for methyl blue is much better than that of P25 (the average particle size of the particles is about 21nm, belonging to the mixed crystal type, anatase and rutile crystal type) particles. However, P5 or smaller photocatalytic particles cannot be used directly in the air. They will be suspended in the air and will disappear when the wind blows. At the same time, traditional photocatalytic materials are difficult to bond with other materials, have small reaction active points, increase the probability of recombination of holes and electrons, have a short lifespan, and can only use ultraviolet light.

[0004] Graphene has a two-dimensional honeycomb crystal structure formed by the close stacking of a single layer of carbon atoms. The unique and perfect structure of graphene gives it excellent electrical, mechanical, thermal and optical properties. Since there are many dangling bonds on the surface of graphene, it can be well bonded with the photocatalytic material. Secondly, graphene has a large specific surface area and high electron mobility, which increases the active points of the reaction, while reducing the recombination of electrons and holes, improving the photocatalytic efficiency. In addition, the presence of graphene narrows the band gap of the titanium dioxide photocatalytic material and increases the utilization rate of sunlight. Therefore, the photocatalytic efficiency can be improved by effectively compounding graphene and titanium dioxide photocatalytic materials. However, the specific surface area of ​​the graphene and titanium dioxide composite photocatalytic materials disclosed now is limited, and in the actual application of air purification, the composite photocatalytic material needs to be loaded on a substrate for use, the loading amount of the substrate is limited, and the contact area and contact time of the composite photocatalytic material on the substrate when the air passes through the purification device once are limited, and the composite photocatalytic material cannot completely and quickly degrade harmful substances such as bacteria and viruses in the air. Therefore, in order to broaden the practical application of composite photocatalytic materials, it is still necessary to develop a graphene and titanium dioxide composite photocatalytic material with a large specific surface area and higher photocatalytic efficiency. Summary of the invention

[0005] The invention aims to solve the problems that the existing graphene and titanium dioxide composite photocatalytic materials have limited specific surface area, and cannot meet the actual application requirements due to insufficient photocatalytic efficiency and limited actual loading amount.

[0006] The present invention provides a nano-composite photocatalytic material, wherein the nano-composite photocatalytic material is a block structure formed by stacking a plurality of spherical titanium dioxide particles with graphene coated on the surface; the block structure of the nano-composite photocatalytic material further comprises a plurality of hole structures connected inside and outside formed by mutually stacking the spherical titanium dioxide particles with graphene coated on the surface; the spherical titanium dioxide particles with graphene coated on the surface comprise an inner layer of spherical titanium dioxide and an outer layer of graphene coating; the spherical titanium dioxide particles with graphene coated on the surface are bonded to each other via dangling bonds on the graphene surface.

[0007] In order to obtain the bulk structure nanocomposite photocatalytic material formed by stacking spherical titanium dioxide particles and having a plurality of internal and external connected pore structures, the present invention adopts the following technical scheme: a method for preparing a nanocomposite photocatalytic material: comprising preparing a nitric acid solution; preparing a butyl titanate solution; preparing a graphene dispersion; preparing a colloidal titanium dioxide solid; heating in an oil bath to prepare spherical titanium dioxide particles coated with graphene; and sintering at a high temperature to stack the spherical titanium dioxide coated with graphene to form a bulk structure.

[0008] Furthermore, the preparation of the nitric acid solution comprises the steps of: pouring a certain volume ratio of 1:1 pure water: anhydrous ethanol into a reactor and stirring for 30 minutes to mix evenly, then adding a certain amount of nitric acid, and continuing to mix and stir for 30 minutes;

[0009] Furthermore, the volume ratio of the added nitric acid to anhydrous ethanol is 1:8-10;

[0010] Furthermore, the preparation of butyl titanate solution comprises the steps of: mixing butyl titanate and anhydrous ethanol in a volume ratio of 2:1, and continuously stirring for 30 minutes;

[0011] Furthermore, the preparation of the graphene dispersion comprises the steps of: firstly putting anhydrous ethanol into a beaker, then adding a certain amount of graphene, and finally putting the beaker into an ultrasonic cleaning machine for ultrasonic dispersion for 30 minutes;

[0012] Furthermore, the graphene is added in an amount of 0.02-0.03 g per 100 ml of anhydrous ethanol;

[0013] Furthermore, the preparation of colloidal titanium dioxide solid comprises the steps of: slowly adding butyl titanate solution to nitric acid solution in a reactor at a rate of 200 ml / min, and continuously stirring so that the color of the mixed solution gradually changes from transparent to light blue, and a colloidal solid is formed;

[0014] Furthermore, the preparation of spherical titanium dioxide particles coated with graphene comprises the steps of: placing a reactor in an oil bath and heating it at a temperature of 110° C. to dissolve the colloidal solid to obtain a milky white liquid, then adding a graphene dispersion and stirring it with a stirrer to evenly disperse the graphene in the milky white liquid, and continuing to heat and stir until the solution in the reactor is completely evaporated to obtain a spherical titanium dioxide solid powder material with a layer of graphene coated on the surface;

[0015] Furthermore, the high-temperature sintering and stacking of graphene-coated spherical titanium dioxide to form a block structure includes the following steps: placing a solid powder in a high-temperature muffle furnace and sintering at 420°C for 2 hours; under the action of graphene, the spherical titanium dioxide particles are bonded and stacked together using the hanging bonds of the graphene to form a composite photocatalytic material with a block structure having multiple internally and externally connected pore structures.

[0016] The formation mechanism of the bulk structure nano-composite photocatalytic material provided by the present invention, which is formed by stacking spherical titanium dioxide particles and having multiple internal and external interconnected pore structures: 1) In the process of preparing nitric acid solution, adding anhydrous ethanol to pure water effectively inhibits the decomposition rate of butyl titanate during the addition process; 2) Butyl titanate is slowly hydrolyzed under the combined action of anhydrous ethanol and nitric acid to form spherical titanium dioxide particles. Nitric acid effectively inhibits the hydrolysis rate of butyl titanate and also promotes the formation of spherical titanium dioxide particles. 3) During the high-temperature sintering process, the spherical titanium dioxide particles are bonded and stacked together using the hanging bonds on the surface of graphene to form a bulk structure composite photocatalytic material containing many spherical titanium dioxide particles coated with graphene on the surface and multiple internal and external interconnected pore structures.

[0017] The nanocomposite photocatalytic material provided by the present invention has the following beneficial effects:

[0018] 1. The composite photocatalytic material is unique in that the spherical titanium dioxide particles with irregular shapes and sizes and coated with graphene on the surface are bonded and stacked to form a bulk structure. The bulk structure formed by the stacking of spherical titanium dioxide particles has a higher specific surface area due to the presence of a pore structure.

[0019] 2. In the actual application of air purification, the block structure and high specific surface area of ​​the composite photocatalytic material can effectively increase its load on the substrate. At the same time, the hole structure in the block structure allows air and ultraviolet light to enter the interior of the block structure, so that when the air is photocatalytically purified, the titanium dioxide particles can contact and disinfect more harmful substances such as bacteria and viruses in the air, thereby greatly improving the photocatalytic efficiency. Verified by a third-party authoritative testing agency, the air purification system prepared using the nano-composite photocatalytic material provided by the present invention has a bacteriophage (MS2) virus removal rate of 93.2% in 5 minutes and 99.94% in 10 minutes. It is proved that the nano-composite photocatalytic material provided by the present invention has an ultra-high photocatalytic degradation efficiency, which effectively improves the photocatalytic degradation efficiency of air passing through the purification device once, thereby further broadening the application scope of the composite photocatalytic material.

[0020] 3. The surface of the spherical titanium dioxide particles of the composite photocatalytic material is coated with a layer of graphene, which enables the titanium dioxide particles to be stacked together through bonding. The block composite material of appropriate size can be selected according to different actual application scenarios. At the same time, graphene also effectively increases the stability of the block structure formed by stacking spherical titanium dioxide particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0022] Figure 1 It is a schematic diagram of the preparation process of the nanocomposite photocatalytic material provided by the present invention.

[0023] Figure 2 This is a SEM photo of the nanocomposite photocatalytic material provided by the present invention.

[0024] Figure 3 It is a schematic diagram of the structure of spherical titanium dioxide particles with graphene coated on the surface of the nano-composite photocatalytic material provided by the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] The present invention provides a nanocomposite photocatalytic material, such as Figure 2 and 3As shown, a block structure 1 is formed by stacking multiple spherical titanium dioxide particles 11 with graphene on the surface; the block structure 1 also includes multiple internally and externally connected hole structures 12 formed by stacking the spherical titanium dioxide particles 11 with graphene on the surface; the spherical titanium dioxide particles 11 with graphene on the surface include an inner spherical titanium dioxide layer 11-2 and an outer graphene coating layer 11-1; the spherical titanium dioxide particles 11 with graphene on the surface are not fixed in shape and have different sizes, and the spherical titanium dioxide particles 11 with graphene on the surface are bonded to each other through dangling bonds on the surface of the graphene 11-1.

[0027] like Figure 1 As shown, the present invention provides a process for preparing a nanocomposite photocatalytic material comprising:

[0028] S01, prepare nitric acid solution

[0029] Pour pure water and anhydrous ethanol in a certain volume ratio of 1:1 into the reactor and stir for 30 minutes to mix evenly, then add a certain amount of nitric acid and continue to mix and stir for 30 minutes; wherein the volume ratio of nitric acid to anhydrous ethanol is 1:8-10;

[0030] S02, preparation of butyl titanate solution

[0031] Mix butyl titanate and anhydrous ethanol in a volume ratio of 2:1 and continue stirring for 30 minutes to obtain a butyl titanate solution;

[0032] S03, preparation of graphene dispersion

[0033] First, put anhydrous ethanol into a beaker, then add a certain amount of graphene, and finally put the beaker into an ultrasonic cleaner for ultrasonic dispersion for 30 minutes; wherein, the amount of graphene added is 0.02-0.03g per 100ml of anhydrous ethanol;

[0034] S04, preparation of colloidal titanium dioxide solid

[0035] The butyl titanate solution is slowly added to the nitric acid solution in the reactor at a rate of 200 ml / min, and the mixture is continuously stirred to gradually change the color of the mixed solution from transparent to light blue. The butyl titanate is slowly hydrolyzed under the combined action of anhydrous ethanol and nitric acid to form colloidal titanium dioxide solid.

[0036] S05, preparation of graphene-coated spherical titanium dioxide particles

[0037] The reactor was placed in an oil bath and heated at 110° C. to dissolve the colloidal solid to obtain a milky white liquid, and then the graphene dispersion of SO3 was added and stirred by a stirrer to evenly disperse the graphene in the milky white liquid. The heating and stirring were continued until the solution in the reactor was completely evaporated to obtain a spherical titanium dioxide solid powder material with a layer of graphene coated on the surface;

[0038] S06, high temperature sintering, graphene-coated spherical titanium dioxide stacked together to form a block structure

[0039] The solid powder is placed in a high-temperature muffle furnace and sintered at 420°C for 2 hours. Under the action of graphene, the spherical titanium dioxide particles are bonded and stacked together using the hanging bonds of graphene to form a composite photocatalytic material with a bulk structure having multiple internal and external connected pore structures.

[0040] Example 1

[0041] S01, prepare nitric acid solution

[0042] Pour 250 ml of pure water and 250 ml of anhydrous ethanol into a reactor and stir for 30 minutes to mix evenly, then add 30 ml of nitric acid, and continue to mix and stir for 30 minutes to obtain a nitric acid solution.

[0043] S02, preparation of butyl titanate solution

[0044] 500 ml of butyl titanate and 250 ml of anhydrous ethanol were mixed and stirred for 30 minutes to obtain a butyl titanate solution.

[0045] S03, preparation of graphene dispersion

[0046] First, put 100 ml of anhydrous ethanol into a beaker, then add 0.0254 g of graphene, and finally put the beaker into an ultrasonic cleaner for ultrasonic dispersion for 30 minutes to obtain a graphene dispersion.

[0047] S04, preparation of colloidal titanium dioxide solid

[0048] The butyl titanate solution obtained from SO2 is slowly added to the nitric acid solution in the reactor at a rate of 200 ml / min, and the mixture is continuously stirred to gradually change the color of the mixed solution from transparent to light blue. The butyl titanate is slowly hydrolyzed under the combined action of anhydrous ethanol and nitric acid to form colloidal titanium dioxide solid.

[0049] S05, Preparation of spherical titanium dioxide particles coated with graphene

[0050] The reactor is placed in an oil bath and heated at 110° C. to dissolve the colloidal solid to obtain a milky white liquid, and then the graphene dispersion obtained by adding SO3 is stirred by a stirrer to evenly disperse the graphene in the milky white liquid. The heating and stirring are continued until the solution in the reactor is completely evaporated to obtain a spherical titanium dioxide solid powder material with a layer of graphene coated on the surface;

[0051] S06, high temperature sintering, the spherical titanium dioxide coated with graphene stacks on each other to form a bulk structure;

[0052] The solid powder obtained from S05 was placed in a high-temperature muffle furnace and sintered at 420°C for 2 hours. Under the action of graphene, the spherical titanium dioxide particles were bonded and stacked together using the hanging bonds of graphene to form a composite photocatalytic material with a bulk structure having multiple internal and external connected pore structures.

[0053] Photocatalytic efficiency detection and practical application of nanocomposite photocatalytic materials:

[0054] The composite photocatalytic material of the block structure with multiple internal and external connected hole structures provided by the present invention is loaded on a plastic substrate by glue bonding to form a photocatalytic module, and the photocatalytic module is installed in the air purifier chassis to form an air purification system. The air purification system is sent to a third-party authoritative testing agency for sterilization and killing efficiency testing of bacteria, viruses, etc. The test results are shown in Table 1 below:

[0055] Table 1:

[0056]

[0057] The composite photocatalytic material provided by the present invention is unique in that the spherical titanium dioxide particles with graphene coated on the surface of the composite photocatalytic material with irregular shapes and different sizes are bonded and stacked to form a block structure. The block structure formed by the stacking of spherical titanium dioxide particles has a higher specific surface area due to the presence of a hole structure. In the actual application of air purification, the block structure and high specific surface area of ​​the composite photocatalytic material can effectively increase its load on the substrate, and the hole structure in the block structure allows air and ultraviolet light to enter the interior of the block structure, so that the titanium dioxide particles can contact and disinfect more harmful substances such as bacteria and viruses in the air during photocatalytic purification of the air, thereby greatly improving the photocatalytic efficiency. Verified by a third-party authoritative testing agency, the air purification system prepared by using the nano-composite photocatalytic material provided by the present invention has a phage (MS2) virus removal rate of 93.2% in 5 minutes and 99.94% in 10 minutes. It is proved that the nano-composite photocatalytic material provided by the present invention has an ultra-high photocatalytic degradation efficiency, which effectively improves the photocatalytic degradation efficiency of air passing through the purification device in a single time, thereby further broadening the application scope of the composite photocatalytic material.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocomposite photocatalytic material, characterized in that: The preparation method of the nanocomposite photocatalytic material comprises: Prepare nitric acid solution; preparing a butyl titanate solution; preparing a graphene dispersion; The butyl titanate solution and the nitric acid solution are mixed to prepare colloidal titanium dioxide solid; Spherical titanium dioxide particles coated with graphene are prepared by heating in an oil bath; After high-temperature sintering, the graphene-coated spherical titanium dioxide stacks up to form a bulk structure; The nanocomposite photocatalytic material is a block structure formed by stacking a plurality of spherical titanium dioxide particles with graphene coated on the surface; the block structure is a plurality of hole structures connected inside and outside formed by stacking the spherical titanium dioxide particles with graphene coated on the surface; the spherical titanium dioxide particles with graphene coated on the surface include an inner layer of spherical titanium dioxide and an outer layer of graphene coating; the spherical titanium dioxide particles with graphene coated on the surface are not fixed in shape and have different sizes; the spherical titanium dioxide particles with graphene coated on the surface are bonded to each other through dangling bonds on the graphene surface; The graphene addition amount is 0.02-0.03g per 100ml of anhydrous ethanol; The method for preparing spherical titanium dioxide particles coated with graphene comprises the following steps: placing a reactor in an oil bath pot and heating it at a temperature of 110° C. to dissolve colloidal titanium dioxide solid to obtain a milky white liquid, then adding a graphene dispersion and stirring it with a stirrer to uniformly disperse the graphene in the milky white liquid, and continuing heating and stirring until the solution in the reactor is completely evaporated to obtain a spherical titanium dioxide solid powder material with a layer of graphene coated on the surface; The high-temperature sintering and stacking of graphene-coated spherical titanium dioxide to form a block structure includes the following steps: placing solid powder in a high-temperature muffle furnace and sintering at 420° C. for 2 hours; under the action of graphene, the spherical titanium dioxide particles are bonded and stacked together using the hanging bonds of the graphene to form a composite photocatalytic material with a block structure having multiple internal and external connected pore structures.

2. The method for preparing the nanocomposite photocatalytic material according to claim 1, characterized in that: The preparation of the nitric acid solution comprises the following steps: pouring a certain volume ratio of 1:1 pure water: anhydrous ethanol into a reactor and stirring for 30 minutes to mix evenly, then adding a certain amount of nitric acid, and continuing to mix and stir for 30 minutes.

3. The method for preparing the nanocomposite photocatalytic material according to claim 1, characterized in that: The volume ratio of the added nitric acid to anhydrous ethanol is 1:8-10.

4. The method for preparing the nanocomposite photocatalytic material according to claim 1, characterized in that: The method for preparing the butyl titanate solution comprises the steps of: mixing butyl titanate and anhydrous ethanol in a volume ratio of 2:1, and continuously stirring for 30 minutes.

5. The method for preparing the nanocomposite photocatalytic material according to claim 1, characterized in that: The method for preparing the graphene dispersion comprises the following steps: firstly putting anhydrous ethanol into a beaker, then adding a certain amount of graphene, and finally putting the beaker into an ultrasonic cleaning machine for ultrasonic dispersion for 30 minutes.

6. The method for preparing the nanocomposite photocatalytic material according to claim 1, characterized in that: The method of mixing a butyl titanate solution and a nitric acid solution to prepare a colloidal titanium dioxide solid comprises the following steps: slowly adding the butyl titanate solution to the nitric acid solution in a reactor at a rate of 200 ml / min, and continuously stirring the mixed solution so that the color of the mixed solution gradually changes from transparent to light blue, and a colloidal titanium dioxide solid is formed.

Citation Information

Patent Citations

  • Preparation method of graphene oxide wrapped titania microsphere photocatalyst

    CN103285845A

  • Graphene / titanium dioxide photocatalysis composite material and preparation method thereof

    CN104084186A